Role of Macronutrient in Better Survival of Critically Sick Neonates Admitted in Neonatal Intensive Care Unit (NICU) (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Neonates are considered more susceptible to macronutrient deficits. During critical illness, sick children cannot normally be fed by mouth, and as a result a pronounced macronutrient deficit often develops after a few days. This macronutrient deficit has been associated with weakness, infections and increased risk of mortality. Therefore, macronutrient as energy source is an important key concern to care and for overall to achieve better survival.Objective: The present study is intended to evaluate the role of macronutrient such as blood glucose, serum calcium, hemoglobin as iron status, serum albumin, in critically sick neonates admitted in NICU and their outcome.Methods: This observational prospective study was carried out at NICU of Dhaka Shishu (Children) Hospital from January 2014 to July 2014. Total 121 neonates were enrolled and analyzed their essential macronutrient profile e.g, blood glucose, serum calcium, hemoglobin, serum albumin and other relevant investigation as complete blood count with film, CRP, blood culture and chest X ray as a part of management as well as to predict their survival.Results: Macronutrient of critically sick neonates play important role to predict their better survival. Perinatal asphyxia and sepsis were major diagnosed pathological conditions of these neonates. In sepsis lower value of serum albumin were statistically significant. Lower value of glucose, calcium, hemoglobin and albumin were also statistically significant in Non-survivors than Survivors.Conclusion: During critical illness in neonates, emphasis should be paid on of adequate macronutrient as energy source. This is necessary for better optimization survival of critically sick neonates.DS (Child) H J 2019; 35(2) : 105-110